QR CODE-BASED PAYMENTS AMONG UPI MANAGEMENT STUDENTS CLASS OF 2022: EXPLORATION OF PERCEPTIONS, ATTITUDES, AND ADOPTION INTENTIONS - Mubarokah, Lailatun; Rahmawati, Nabila; Rizky, Rafly Muhammad (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This article discusses a study that analyzes the use of payments through QR codes among students majoring in Management of the class of 2022 Universitas Pendidikan Indonesia (UPI). The research method used is a survey with a questionnaire distributed to UPI Management students of the class of 2022. The data was then analyzed using linear regression techniques to test the relationship between the use of payments through QR codes and the propensity of student payments. Additionally, the article employs the Rasch Model, one of the item response theories, which describes the relationship between respondent ability and the level of item difficulty. The results of the study show that the use of payment through QR codes has a significant impact on the payment trend of UPI Management students. These findings provide insight into student payment trends and their implications in the context of the use of payment technology in higher education.